(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: Snakebite is a medical emergency resulting in significant morbidity and mortality globally. Snakebite, in Nepal presents a complicated medical situation, characterized by unique clinical features, treatment approaches, and outcomes. Therefore, there is an increasing demand for scholarly research into the effective care and management of snakebites in Nepal. This retrospective study aims to analyze the clinical characteristics, treatment approach and outcome of snakebites at a tertiary care facility in Pokhara, Nepal. Materials and Methods: Medical records of snakebite patients admitted to the tertiary care facility for a period of one year (August 30, 2018 to August 30, 2019) were retrospectively reviewed. Data on demographics, clinical features, and treatment approaches were collected and analyzed. Results: A total of 247 snakebite cases were included in the study. The results of clinical presentation revealed that the majority of cases (61.5%) had no fang marks. Similarly, majority of patients had cellulitis (68.4%), pain and swelling (29.1%), change in skin color (22.7%), and vesicles and bullae (2.0%). Neurological symptoms were not present in any cases (100.0%). 72.5% of patients experienced no bleeding, while 19.8% exhibited external bleeding and 7.7% had internal bleeding. Fresh frozen plasma was administered among 94 (38.1%) of snakebite patients admitted to the hospital. Hospital stays were brief, with 79.4% of patients staying less than 5 days with only 19.0% being referral cases. The findings of treatment approach indicated that anti-snake venom was not used in any reported cases. Finally, the outcome showed improving condition in all the cases with no use of anti -venom. Conclusions: This retrospective analysis provides insights into the clinical characteristics and treatment patterns of snakebites, highlighting patterns and areas for further investigation and improvement in treatment protocols particularly the use of anti-snake venom